Maastrichtian ammonites from the United Arab Emirates-Oman border region - Kennedy, W (1995)
The ammonites described are from the late Cretaceous Qahlah and Simsima Formations of the United Arab Emirates-Oman border region and come from two collections. Some of the specimens were collected by Dr. P.W. Skelton (Open University) in 1990 and are housed in Oxford University Museum. The remainder are housed in the Natural History Museum, London and were mostly collected by A.B. Smith and N.J. Morris during fieldwork in 1991 and 1992. Wherever possible, ammonites have been tied down to specific levels within measured sections. -from Author